IMPROVING THE ACCOUNTING OF LEASING OPERATIONS IN COMMERCIAL BANKS: https://doi.org/10.5281/zenodo.15621604 - Umarova , Lola (Journal of Contemporary World Studies, 2025)
This article analyzes the importance of leasing operations in the activities of commercial banks and the mechanisms of their accounting. Accurate and correct accounting of leasing operations and their proper reflection in financial statements are of great significance for banks. The article develops proposals and recommendations to address the problems arising in the accounting of leasing operations based on current national and international accounting standards.